Correlation between bisphenol A. perfluorooctanoic acid, and polychlorinated biphenyls and uridine diphosphate glucuronyltransferase Polymorphisms in metabolic syndrome patients / Dr. Normala Abd. Latip and Sabreenna Marsya Djuli - Abd. Latip, Normala; Djuli, Sabreenna Marsya (Faculty of Pharmacy, 2023)
Endocrine-disrupting chemicals (EDCs) are exogenous chemicals which are able to interfere with hormone action. They are emerging as significant environmental contaminants, particularly in food and water. Although there are many synthetic chemicals that may be considered as EDCs due to their endocrine-disrupting properties, there are a number of classes which are most commonly studied. These include phenolic compounds, phthalates, polyhalogenated compounds, polycyclic aromatic compounds, pesticides, and pharmaceuticals.